Assessment of quality indicators of the automatic control system influence of accident interference - Igor Parkhomey; Juliy Boiko; Nataliia Tsopa; Iryna Zeniv; Oleksander Eromenko (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This work concentrates the analysis of the system of automatic control of the directive diagram of the moving active electronically scanned array with a limited number of transceiver modules. The analysis revealed a number of shortcomings that lead to a significant increase in standard deviations, quadratic integral estimates, and an increase in transient time. The identified disadvantages lead to a decrease in the efficiency of the antenna system, an increase in the error rate at the reception, the inability of the system to react to disturbances applied to any point of the system in the event of a mismatch of a given signal/noise level. In accordance with the analysis, the mathematical model of the automatic control system of the directional diagram of the moving active electronically scanned array was considered, considering this a new method of estimating the quality indicators of the automatic control diagram of the directional diagram of the active electronically scanned array in a random setting and disturbing action was developed. The difference between the proposed method and the existing method is in the construction of an automatic control system with differential coupling equivalent to the combination due to the introduction of derivatives of the random setting action of the open compensation connection.